1971
DOI: 10.1002/kin.550030108
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine‐photosensitized oxidations of chloroethanes and chloroethylenes in the gas phase

Abstract: Long-chain chlorine-photosensitized oxidation has been observed in the gas phase at about 355'K for 1,1,2,2-and 1,1,1,2-C~H~C14, CZHClS, and CzC14 but not for CzHe, 1,2-CzH4C12, I,l,I-C2H3C13, CzH4, and 1,2-CzHzCIz. This is shown to depend on the exothermicity of the dissociation of the chloroethoxy radicals which must be involved in each reaction system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…The further decomposition of CClO' is a potential source 0, + *cc1,cc1(0) -'oocc1,cc1(o) of the observed carbon monoxide CClO' -c1+ co (15) The experiments in which the yield of the DCAC increased with decreasing reactor radius are a result of the competition between TCE and DCAC for reactive species on or near the surface. With the larger reactors, bulk diffusion limits the access of the TCE to the area near the surface and the DCAC can more effectively compete for reactive species.…”
Section: Discussionmentioning
confidence: 99%
“…The further decomposition of CClO' is a potential source 0, + *cc1,cc1(0) -'oocc1,cc1(o) of the observed carbon monoxide CClO' -c1+ co (15) The experiments in which the yield of the DCAC increased with decreasing reactor radius are a result of the competition between TCE and DCAC for reactive species on or near the surface. With the larger reactors, bulk diffusion limits the access of the TCE to the area near the surface and the DCAC can more effectively compete for reactive species.…”
Section: Discussionmentioning
confidence: 99%
“…In all three of these cases, it can be seen that the branching ratios between CC, CCl, and where possible, CH bond scission are a reasonable reflection of the thermochemistry. That is, in all cases, the most favored unimolecular process is the most exothermic pathway, although it should be appreciated that the uncertainties in the values of Δ r H ° are large since the values of Δ f H ° for the chlorinated ethoxy radicals are only estimates based on group additivity rules …”
Section: CL Atom Initiated Oxidation Of H2cccl2 Clhcchcl and Clhcc...mentioning
confidence: 99%
“…In the case of the oxidation of C 2 Cl 4 , it seemed reasonable to suppose that this species might be involved in this additional reaction and one possible step that would influence the yields of products in the manner that is observed is This reaction is thermodynamically allowed, being exothermic by −128 kJ mol -1 , and, if it were fast enough to compete with the unimolecular decompositions R5d and R6d, its occurrence would explain why higher initial concentrations of C 2 Cl 4 result in higher yields of CCl 3 COCl and decreased yields of COCl 2 . The reaction is also exothermic, although reaction to produce C 2 Cl 5 + COCl 2 is possible.…”
Section: CL Atom Initiated Oxidation Of Cl2cccl2 and Cl3cccl2h:  Dis...mentioning
confidence: 99%
“…On the other hand, C2H4 does not oxidize through a long chain, and the details of the oxidation are quite different. Bertrand et al 14 reported that the chlorine-atom initiated oxidation has a chain length less than 2 at room temperature. The reaction of 0(3P) with C2H4 has been extensively examined.…”
Section: Introductionmentioning
confidence: 99%